Markedly Increased IP-10 Production by Blood-Brain Barrier in Neuromyelitis Optica - Shimizu, Fumitaka (PLoS One, 2015)
OBJECTIVE: Severe damage to the blood-brain barrier (BBB) allows anti-aquaporin 4 (AQP4) antibodies to access the astrocytic endfeet in neuromyelitis optica (NMO). In the current study, we identified the pathogenic cytokines/chemokines that are responsible for the BBB malfunction induced by NMO sera. METHODS: We measured the levels of 27 cytokines/chemokines in human brain microvascular endothelial cells (BMECs) after exposure to sera obtained from patients with the acute and stable phases of anti-AQP4 antibody-positive NMO spectrum disorder (NMOSD), multiple sclerosis (MS) patients and healthy controls (HC) using a multiplexed fluorescent bead-based immunoassay system. RESULTS: The induced protein (IP)-10 level in the cells was markedly increased following exposure to acute phase NMOSD sera. Other cytokines/chemokines including interleukin (IL)-6 and monocyte chemotactic protein (MCP)-1 were also significantly increased in the acute NMOSD group compared to both the MS and HC groups. The up-regulation of the IP-10 levels in the cells after exposure to the acute-phase NMOSD sera was also observed using another specified ELISA, and this effect was significantly decreased during the remission phase in the individual NMOSD patients. Furthermore, the increase in the level of IP-10 after exposure to the sera was significantly correlated with the cerebrospinal fluid/serum albumin ratio. CONCLUSIONS: Sera from the acute phase of NMO markedly increased the autocrine secretion of IP-10 by BMECs. The over-production of IP-10 in BMECs may play an important role in the pathogenesis of NMO and may therefore help to mediate the trafficking of T cells expressing its receptor across the BBB.